Persistence of cerebellar ataxia during chronic ethanol exposure is associated with epigenetic up‐regulation of Fmr1 gene expression in rat cerebellum. (28th August 2021) - Dulman, Russell S.; Auta, James; Wandling, Gabriela M.; Patwell, Ryan; Zhang, Huaibo; Pandey, Subhash C.
Abstract: Background: Alcohol intoxication produces ataxia by affecting the cerebellum, which coordinates movements. Fragile X mental retardation (FMR) protein is a complex regulator of RNA and synaptic plasticity implicated in fragile X‐associated tremor/ataxia syndrome, which features ataxia and increased Fmr1 mRNA expression resulting from epigenetic dysregulation of FMRP. We recently demonstrated that acute ethanol‐induced ataxia is associated with increased cerebellar Fmr1 gene expression via histone modifications in rats, but it is unknown whether similar behavioral and molecular changes occur following chronic ethanol exposure. Here, we investigated the effects of chronic ethanol exposure on ataxia and epigenetically regulated changes in Fmr1 expression in the cerebellum. Methods: Male adult Sprague‐Dawley rats were trained on the accelerating rotarod and then fed with chronic ethanol or a control Lieber–DeCarli diet while undergoing periodic behavioral testing for ataxia during ethanol exposure and withdrawal. Cerebellar tissues were analyzed for expression of the Fmr1 gene and its targets using a real‐time quantitative polymerase chain reaction assay. The epigenetic regulation of Fmr1 was also investigated using a chromatin immunoprecipitation assay. Results: Ataxic behavior measured by the accelerating rotarod behavioral test developed during chronic ethanol treatment and persisted at both the 8‐h and 24‐h withdrawal time points compared to control diet‐fed rats. In addition, chronic ethanol treatment resulted in up‐regulated expression of Fmr1 mRNA and increased activating epigenetic marks H3K27 acetylation and H3K4 trimethylation at 2 sites within the Fmr1 promoter. Finally, measurement of the expression of relevant FMRP mRNA targets in the cerebellum showed that chronic ethanol up‐regulated cAMP response element binding (CREB) Creb1, Psd95, Grm5, and Grin2b mRNA expression without altering Grin2a, Eaa1, or histone acetyltransferases CREB binding protein ( Cbp ) or p300 mRNA transcripts. Conclusions: These results suggest that epigenetic regulation of Fmr1 and subsequent FMRP regulation of target mRNA transcripts constitute neuroadaptations in the cerebellum that may underlie the persistence of ataxic behavior during chronic ethanol exposure and withdrawal. Abstract : Cerebellar ataxia caused by ethanol exposure plays an important role in alcohol use disorder. Behavioral data collected in this study show that ataxia develops during chronic ethanol exposure and persists during acute withdrawal. Biochemical data suggest that epigenetic regulation of Fragile X Mental Retardation (FMR) gene Fmr1 and subsequent changes in its target mRNA transcripts constitute an important molecular mechanism in the cerebellum that may underlie persistence of ataxic behavior during chronic ethanol exposure and withdrawal.